Anisotropic electromagnetic interference shielding properties of polymer-based composites with magnetically-responsive aligned Fe3O4 decorated reduced graphene oxide. (15th March 2020) - Hong, Sung Yong; Kim, Ye Chan; Wang, Mei; Nam, Jae-Do; Suhr, Jonghwan
Graphical abstract: Highlights: The magnetically-responsive Fe3 O4 @RGO was synthesized for EMI shielding materials. The orientations of Fe3 O4 @RGO in TPU were controlled by applying magnetic field. Thereby, the highly anisotropic EMI shielding composites were demonstrated. The 250% improvement in EMI SE were achieved by controlling orientation of filler. Abstract: Recently, polymer-based composites for electromagnetic interference (EMI) shielding materials have received considerable attention since the autonomous vehicle market is increasingly growing. However, the strategies for enhancing EMI shielding effectiveness (EMI SE) are limited to the increase of filler loading. Only few studies have been conducted on controlling fillers owing to the technical challenges. In this study, anisotropic EMI shielding properties of polymer-based composites were demonstrated and investigated. In order to control the orientation of reduced graphene oxide (RGO) in thermoplastic polyurethane (TPU), magnetic responsive RGO (Fe3 O4 @RGO) was synthesized for filler material. The orientation of Fe3 O4 @RGO was controlled in in-plane and out-of-plane direction by applying the magnetic field. For comparison with the aligned Fe3 O4 @RGO/TPU composites, random Fe3 O4 @RGO/TPU and random RGO/TPU composites were synthesized and characterized. The random Fe3 O4 @RGO/TPU composites showed 224% increased EMI SE over random RGO/TPU composites. The highest EMI SE, 250% improvement over random RGO/TPU composite, was observed in in-plane aligned Fe3 O4 @RGO composite among the four different composites. This could be attributed to improved electromagnetic wave (EM) loss by introducing magnetic nanoparticles, as well as enlarged effective reflection area of the aligned Fe3 O4 @RGO. Our results confirm that the orientation of fillers can play a key role in determining EMI SE in the composites. It can indicate that, if optimized, magnetically-responsive aligned polymer composites could significantly improve EMI SE of the composites by controlling the orientation of fillers, and also be a new solution to create anisotropic composites toward desirable properties.